Atmospheric Rivers Contribution to the Snow Accumulation Over the Southern Andes (26.5° S–37.5° S) - Saavedra, Felipe; Cortés, Gonzalo; Viale, Maximiliano; Margulis, Steven; McPhee, James (Frontiers in Earth Science, 2020)
This paper quantifies the climatological contribution of atmospheric rivers (ARs) to annual snow accumulation in the Andes Cordillera between 26.5° S and 36.5° S. An AR identification algorithm, and a high-resolution (0.01°) snow reanalysis dataset, both especially developed for this mountainous region, are used for this quantification over the 1984-2014 period. Results show that AR snowfall events explain approximately 50% of the annual snow accumulation over the study area, and are 2.5 times more intense than non-AR snowfall events. Due to orographic precipitation enhancement on the western slopes and a prominent rain shadow effect on the eastern slopes, annual snow accumulation and AR storms contribution to this accumulation are, on average, 7 and 12 times larger on western than on eastern slopes of the mountain range, respectively. Areas with lower peak elevations see more spillover snowfall over the eastern slopes of the mountain range, especially south of 35° S. Analysis of teleconnections with El Niño Southern Oscillation shows a reduction in the AR frequency across the study area during La Niña episodes and, consequently, a lower contribution to snow accumulation. Conversely, weak and moderate El Niño episodes show an increase in AR frequency, and consequently more snowfall.